Integrated system of progressive freeze-concentration combined with partial ice-melting for yield improvement. (September 2016) - Miyawaki, Osato; Omote, Chiakai; Gunathilake, Mihiri; Ishisaki, Kana; Miwa, Syouji; Tagami, Ayana; Kitano, Shigeru
Abstract: A 25L-scale tubular ice system for progressive freeze-concentration was constructed and combined with a 75L-scale partial ice-melting system for yield improvement. From the measurement of freezing point of various fruits juices, nine standard operation programs were prepared in cooling and circulation flow rate for the tubular ice system. The standard programs were successfully tested for progressive freeze-concentration of sucrose solutions with concentration varied from 3 to 30%. By choosing one of the standard program, apple juice was effectively concentrated from 12.8 to 21.0 °Brix with 79.0% yield, which was improved to 90% by recovering the 30% of the initially-melted fractions by using the partial ice-melting system. The tubular ice system can be easily scaled-up more, if necessary, simply by increasing the number of tubes. Highlights: A 25 L scale tubular ice system for progressive freeze-concentration was constructed. The above system was combined with 75 L scale partial ice-melting system. Standard programs were prepared in cooling and circulation for tubular ice system. Standard programs were effective to concentrate sucrose solutions and apple juice. Partial ice-melting system effectively improved yield for high-concentration sample.